PERAN PSDKP LAMPULO DALAM PENGAWASAN DAN PENANGANAN KASUS DESTRUCTIVE FISHING DI PERAIRAN ACEH PADA MASA PANDEMI COVID-19 - Ahmad Muhammad Mirza; Ade Irma Suryani Nasution; Yudhawira Bhaskara Sembiring; Moch Jurianto; Rudiyanto Rudiyanto; Panji Suwarno (Jurnal Education and Development, 2021)
Destructive fishing cases occur in various regions in Indonesia, one of which is Aceh Province. The case of Destructive fishing is nothing new for Aceh. Aceh Province ranks 4th as a province with many cases of destructive fishing. This research was conducted using a qualitative method through interviews with the Head of PSDKP Lampulo and equipped with a literature study, and the research data presented descriptively. Destructive fishing is an activity that violates the law because it takes fish resources by damaging the environment around where the fish live. People who do destructive fishing usually use explosives in the form of bombs and use toxic materials to catch fish. Declining economic activity due to the negative impact of the Covid-19 pandemic can also be one of the factors that encourage destructive fishing to be carried out. Based on data obtained from sources, as for the types of destructive fishing in Aceh waters during the pandemic, fishing using bombs was 23.53%, using poison 39.71%, using electric shocks 41.12%, and using compressors 33.82%, and using trawling by 25%. So the dominant destructive fishing gear used is to use a stun. The handling of Destructive fishing cases by the Lampulo PSDKP Base in Aceh Province Waters during the pandemic was carried out through methods of supervision, inspection, investigation, and prevention of Destructive fishing cases. PSDKP Lampulo has an active role, namely supervision, as well as a participatory role, namely examination, investigation, and prevention that have been running effectively.